Gut microbiota, nutrition, and mental health - Merlo, Gia; Bachtel, Gabrielle; Sugden, Steven G. (Frontiers in Nutrition, 2024)
The human brain remains one of the greatest challenges for modern medicine, yet it is one of the most integral and sometimes overlooked aspects of medicine. The human brain consists of roughly 100 billion neurons, 100 trillion neuronal connections and consumes about 20-25% of the body's energy. Emerging evidence highlights that insufficient or inadequate nutrition is linked to an increased risk of brain health, mental health, and psychological functioning compromise. A core component of this relationship includes the intricate dynamics of the brain-gut-microbiota (BGM) system, which is a progressively recognized factor in the sphere of mental/brain health. The bidirectional relationship between the brain, gut, and gut microbiota along the BGM system not only affects nutrient absorption and utilization, but also it exerts substantial influence on cognitive processes, mood regulation, neuroplasticity, and other indices of mental/brain health. Neuroplasticity is the brain's capacity for adaptation and neural regeneration in response to stimuli. Understanding neuroplasticity and considering interventions that enhance the remarkable ability of the brain to change through experience constitutes a burgeoning area of research that has substantial potential for improving well-being, resilience, and overall brain health through optimal nutrition and lifestyle interventions. The nexus of lifestyle interventions and both academic and clinical perspectives of nutritional neuroscience emerges as a potent tool to enhance patient outcomes, proactively mitigate mental/brain health challenges, and improve the management and treatment of existing mental/brain health conditions by championing health-promoting dietary patterns, rectifying nutritional deficiencies, and seamlessly integrating nutrition-centered strategies into clinical care.